A Review of Research on Teaching People With Significant Disabilities Vocational Skills. (May 2017) - Cannella-Malone, Helen I.; Schaefer, John M.
Although an important part of adult life, individuals with significant disabilities experience low rates of gainful employment. The purpose of this review was to summarize and analyze the literature on teaching vocational skills to individuals with significant disabilities. Sixty-two articles (with 75 experiments) included in this review were published between 1969 and 2014, and indicated that most participants were successfully taught to engage in a variety of vocational skills in a range of settings. Unfortunately, this review also determined that the research on teaching vocational skills to individuals with significant disabilities is steadily decreasing, with only 15 new studies published since 2000. Potential directions for future research will be proposed.